Stable DNA Nanomachine Based on Duplex–Triplex Transition for Ratiometric Imaging Instantaneous pH Changes in Living Cells - Yang, Mengqi (Anal Chem, 2015)
[Image: see text] DNA nanomachines are becoming useful tools for molecular recognition, imaging, and diagnostics and have drawn gradual attention. Unfortunately, the present application of most DNA nanomachines is limited in vitro, so expanding their application in organism has become a primary focus. Hence, a novel DNA nanomachine named t-switch, based on the DNA duplex–triplex transition, is developed for monitoring the intracellular pH gradient. Our strategy is based on the DNA triplex structure containing C(+)-G-C triplets and pH-dependent Förster resonance energy transfer (FRET). Our results indicate that the t-switch is an efficient reporter of pH from pH 5.3 to 6.0 with a fast response of a few seconds. Also the uptake of the t-switch is speedy. In order to protect the t-switch from enzymatic degradation, PEI is used for modification of our DNA nanomachine. At the same time, the dynamic range could be extended to pH 4.6–7.8. The successful application of this pH-depended DNA nanomachine and motoring spatiotemporal pH changes associated with endocytosis is strong evidence of the possibility of self-assembly DNA nanomachine for imaging, targeted therapies, and controllable drug delivery.